Motivasi Internal dan Eksternal Pemakaian Gigi Tiruan pada Lansia - Sukini Sukini; Betty Saptiwi; Wahyu Jati Dyah Utami (Jurnal LINK, 2015)
This research aims to observe the motivation of denture-using on PoltekkesSemarang’s elders community “Sehat Bugar". This observation research was conducted in August until September 2014. The sample used in this research was the total samples of 67 subjects. The results of the Chi Square correlation analysis shows there is significant relationship between Internal motivation and the use of denture with 0.012 (p 0.05) and there was no relationship between external motivation and the use of denture with 0.604 (p0.05).